Hua Jong Wei Die - Dongdong, Wang; Yu, Chang (China : Dongdong, Wang, 2005)
Acrobatics are one of the first performance arts that comes to mind when we think of China. Little children are coming from all over China to Hei Long Jiang Acrobatic Troupe with hope of becoming professional acrobats one day. Their main reason for coming to this place despite its strict discipline and hardships is to provide their family with economic support. However, few can achieve their goals. We see their hardhsips through one girl who can no longer afford lessons and a boy who is hospitalized because of an injured leg during training and who ponders whether the troupe can gaurantee his future. By listening to each child's story, "Growing Up" portrays these children's hopes, their responsibilities to their family, their apprehnsions, and the hidden part of China's acrobatic industry.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films